2019
DOI: 10.1016/j.neuroimage.2019.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The representation of symmetry in multi-voxel response patterns and functional connectivity throughout the ventral visual stream

Abstract: Several computational models explain how symmetry might be detected and represented in the human brain. However, while there is an abundance of psychophysical studies on symmetry detection and several neural studies showing where and when symmetry is detected in the brain, important questions remain about how this detection happens and how symmetric patterns are represented. We studied the representation of (vertical) symmetry in regions of the ventral visual stream, using multi-voxel pattern analyses (MVPA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 39 publications
10
36
0
Order By: Relevance
“…The finding that V3 represents shape skeletons is consistent with human neuroimaging studies showing its involvement in perceptual organization (Sasaki, 2007). Indeed, V3 has been consistently implicated in creating shape percepts (Caplovitz, Barroso, Hsieh, & Tse, 2008;McMains & Kastner, 2010;Montaser-Kouhsari, Landy, Heeger, & Larsson, 2007) and is the earliest stage of the visual hierarchy where symmetry structure has been decoded (Keefe et al, 2018;Sasaki, Vanduffel, Knutsen, Tyler, & Tootell, 2005;Van Meel, Baeck, Gillebert, Wagemans, & Op de Beeck, 2019). But how might shape skeletons arise in V3?…”
Section: Discussionsupporting
confidence: 70%
“…The finding that V3 represents shape skeletons is consistent with human neuroimaging studies showing its involvement in perceptual organization (Sasaki, 2007). Indeed, V3 has been consistently implicated in creating shape percepts (Caplovitz, Barroso, Hsieh, & Tse, 2008;McMains & Kastner, 2010;Montaser-Kouhsari, Landy, Heeger, & Larsson, 2007) and is the earliest stage of the visual hierarchy where symmetry structure has been decoded (Keefe et al, 2018;Sasaki, Vanduffel, Knutsen, Tyler, & Tootell, 2005;Van Meel, Baeck, Gillebert, Wagemans, & Op de Beeck, 2019). But how might shape skeletons arise in V3?…”
Section: Discussionsupporting
confidence: 70%
“…The extrastriate symmetry response increases with the degree of regularity in wallpaper patterns ( Kohler, Clarke, Yakovleva, Liu, & Norcia, 2016 ) and the proportion of symmetry in symmetry + noise displays ( Keefe et al., 2018 ; Sasaki et al., 2005 ). Recently, van Meel, Baeck, Gillebert, Wagemans and Op de Beeck (2019) found that the distinction between symmetrical and asymmetrical dot patterns can be reliably decoded from patterns of voxel activations in LOC. Transcranial magnetic stimulation work provides converging evidence: For example, Bona, Herbert, Toneatto, Silvanto and Cattaneo (2014) found that disruption of LOC selectively impairs symmetry discrimination (see also Bona, Cattaneo, & Silvanto, 2015 ; Cattaneo, Mattavelli, Papagno, Herbert, & Silvanto, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent psychophysical (Kelly et al, 2001; Kurki & Saarinen, 2004; Seu & Ferrera, 2001) and neuroscientific results (Ostwald et al, 2008;Pei et al, 2005) corroborate this theory. Functional MRI in monkeys and humans has identified symmetry-related activations in areas V4 and LOC but not areas V1 or V2 (Chen et al, 2007;Keefe et al, 2018;Kohler et al, 2016;Sasaki et al, 2005;Tyler et al, 2005;Van Meel et al, 2019). Van Meel et al (2019) suggest a gradual change from part-base coding in areas V1-V2, to computation of more complex features in V4, to final global symmetry representation in LOC.…”
Section: Discussionmentioning
confidence: 99%
“…It has negative amplitude and is generated by neurons in the extrastriate cortex and lateral occipital complex (LOC; Makin et al, 2016;Rampone, Makin, Tatlidil, & Bertamini, 2019). The SPN is a well-characterised neural signal, and its interpretation is consistent with fMRI (Chen, Kao, & Tyler, 2007;Keefe et al, 2018;Kohler, Clarke, Yakovleva, Liu, & Norcia, 2016;Sasaki, Vanduffel, Knutsen, Tyler, & Tootell, 2005;Tyler et al, 2005;Van Meel, Baeck, Gillebert, Wagemans, & Op de Beeck, 2019) and TMS evidence (Bona, Cattaneo, & Silvanto, 2016;Bona, Herbert, Toneatto, Silvanto, & Cattaneo, 2014;Cattaneo et al, 2014;Cattaneo, Bona, & Silvanto, 2017). Makin et al (2016) tested specific predictions of the holographic model.…”
Section: Introductionmentioning
confidence: 88%